Polymer microsphere and preparation method thereof
Patent Information
- Application Number
- CN202380008403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2024-12-20
AI Technical Summary
Existing magnetic nano- or micro-composites have problems with poor magnetic response and unstable magnetic adsorption in biomedical applications, mainly due to size limitations and insufficient thermal stability.
It adopts the structure of polymer microspheres, which includes a core body and a shell surrounding the core body. The core body contains at least two magnetic particles and a dispersion. The shell is composed of the same material and is formed in one step through an in-situ polymerization method. The dispersion, The shell body and the modified layer are made of the same material and contain functional functional groups to ensure that the interfaces between the magnetic particles are separated and avoid mutual melting under thermal cycle conditions.
The magnetic response effect and adsorption force stability of magnetic microspheres are improved, the preparation process is simplified and the cost is reduced, and the detection accuracy and usage efficiency in biomedical applications are enhanced.
Smart Images

Figure CN119173965A_ABST
Abstract
Description
Polymer microspheres and preparation method thereof Technical Field
[0001] The present application relates to the field of biomedicine, and in particular to polymer microspheres and a preparation method thereof. Background Art
[0002] Magnetic nano- or micro-composites, such as magnetic microspheres, have attracted widespread attention due to their potential applications in biomedicine. However, existing magnetic microspheres suffer from poor magnetic response or unstable magnetic adsorption due to size limitations and thermal stability. There is an urgent need for novel magnetic microspheres to address these challenges.
[0003] Summary of the Invention
[0004] The embodiments of this application adopt the following technical solutions:
[0005] In a first aspect, an embodiment of the present application provides a polymer microsphere, comprising a core and a shell encapsulating the core;
[0006] The core comprises at least two magnetic particles and a dispersion located between two adjacent magnetic particles; the shell comprises a shell body and a modification layer, wherein the modification layer is located on a side of the shell body away from the magnetic particles;
[0007] The dispersion, the housing body and the modification layer are made of the same material.
[0008] In at least one embodiment of the present application, the dispersion covers at least a portion of the surface of the magnetic particles.
[0009] In at least one embodiment of the present application, the materials of the dispersion, the shell body and the modified layer all include a polymer formed by at least one first monomer and at least one second monomer; the molar ratio of the first monomer to the second monomer ranges from 0.1 to 10.
[0010] In at least one embodiment of the present application, the second monomer and the modified layer both include at least one group selected from the group consisting of amino, carboxyl, hydroxyl, and silanol.
[0011] In at least one embodiment of the present application, the molar amount of the second monomer is less than the molar amount of the first monomer.
[0012] In at least one embodiment of the present application, the first monomer includes at least one of styrene, butadiene, pentadiene, isoprene, methyl acrylate, acrylonitrile, methyl methacrylate, and tetraethyl orthosilicate;
[0013] The second monomer includes at least one of methacrylic acid, ethyleneimine, hydroxyethylpropylene, tetraethyl orthosilicate, vinylsiloxane, N-(4-carboxyphenyl)maleimide, aminopropyltriethoxysilane and glyoxal.
[0014] In at least one embodiment of the present application, the ratio of the mass of the magnetic particle to the sum of the masses of the first monomer and the second monomer is in a range of 0.5 to 3.
[0015] In at least one embodiment of the present application, the first monomer includes styrene, the second monomer includes methacrylic acid, and the molar ratio of the first monomer to the second monomer ranges from 0.1 to 10.
[0016] In at least one embodiment of the present application, the first monomer includes tetraethyl orthosilicate, the second monomer includes aminopropyltriethoxysilane and glyoxal, the molar ratio of the first monomer to the total amount of monomers ranges from 0.1 to 0.8, the molar ratio of aminopropyltriethoxysilane to the total amount of monomers in the second monomer ranges from 0.1 to 0.4, and the molar ratio of glyoxal in the second monomer to the total amount of monomers ranges from 0.1 to 0.5.
[0017] In at least one embodiment of the present application, the first monomer includes styrene, the second monomer includes ethyleneimine, the molar ratio of the first monomer to the total amount of monomers ranges from 0.1 to 0.6, and the molar ratio of the second monomer to the total amount of monomers ranges from 0.4 to 0.9.
[0018] In at least one embodiment of the present application, the distance between the magnetic particle and the modified layer in the direction from the geometric center of the polymer microsphere to the modified layer ranges from 10 nm to 500 nm.
[0019] In at least one embodiment of the present application, the magnetic particles include a combination of one or more of iron oxide, cobalt oxide, and nickel oxide, and the size of the magnetic particles ranges from 8 nm to 15 nm.
[0020] In at least one embodiment of the present application, the size of the polymer microspheres ranges from 100 nm to 5 μm.
[0021] In a second aspect, embodiments of the present application provide a method for preparing polymer microspheres, which is used to prepare the polymer microspheres as described in any one of the first aspects, the method comprising:
[0022] forming magnetic particles;
[0023] The magnetic particles, at least one first monomer and at least one second monomer are mixed together, and the polymer microspheres are formed in one step by in-situ polymerization; wherein the polymer microspheres include a core and a shell that wraps the core; the core includes at least two magnetic particles and a dispersion located between two adjacent magnetic particles; the shell includes a shell body and a modified layer, and the modified layer is located on the side of the shell body away from the magnetic particles; wherein the dispersion, the shell body and the modified layer are made of the same material and all include a polymer formed by at least one first monomer and at least one second monomer.
[0024] In at least one embodiment of the present application, the step of mixing the magnetic particles, at least one first monomer, and at least one second monomer to form the polymer microspheres in one step by in-situ polymerization comprises:
[0025] The magnetic particles, one of the first monomers, and one of the second monomers are mixed together to form the polymer microspheres in one step by in-situ polymerization;
[0026] Alternatively, the magnetic particles, one first monomer and two second monomers are mixed together, and the polymer microspheres are formed in one step by in-situ polymerization.
[0027] In at least one embodiment of the present application, when the magnetic particles, one first monomer, and one second monomer are mixed together and the polymer microspheres are formed in one step by in-situ polymerization, the step includes:
[0028] dispersing the magnetic particles in anhydrous ethanol to obtain a suspension of the magnetic particles;
[0029] Adding polyvinyl pyrrolidone, an initiator, and the second monomer to the suspension of the magnetic particles, introducing a protective gas; after stirring evenly, adding the first monomer, and continuously stirring and reacting at a first preset temperature for 2 to 6 hours; wherein the first monomer includes styrene and the second monomer includes methacrylic acid;
[0030] After the reaction solution is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain the polymer microspheres.
[0031] In at least one embodiment of the present application, when the magnetic particles, one first monomer, and one second monomer are mixed together and the polymer microspheres are formed in one step by in-situ polymerization, the step includes:
[0032] dispersing the magnetic particles in anhydrous ethanol to obtain a suspension of the magnetic particles;
[0033] Adding polyvinyl pyrrolidone, an initiator, the first monomer, and the second monomer to the suspension of the magnetic particles; stirring continuously for 2 to 4 hours under vacuum and a second preset temperature; wherein the first monomer includes styrene and the second monomer includes ethyleneimine;
[0034] After the reaction solution is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain the polymer microspheres.
[0035] In at least one embodiment of the present application, when the magnetic particles, one first monomer, and two second monomers are mixed together and the polymer microspheres are formed in one step by in-situ polymerization, the step includes:
[0036] dispersing the first monomer in anhydrous ethanol;
[0037] dispersing the magnetic particles in an aqueous solution containing polyvinyl pyrrolidone to obtain a suspension of the magnetic particles;
[0038] Adding the suspension of magnetic particles to anhydrous ethanol in which the first monomer is dispersed, then adding two second monomers and ammonia water, stirring evenly and reacting at a third preset temperature for 1 to 3 hours; wherein the first monomer includes tetraethyl orthosilicate, and the second monomer includes aminopropyltriethoxysilane and glyoxal;
[0039] After the reaction solution is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain the polymer microspheres.
[0040] In at least one embodiment of the present application, forming magnetic particles comprises:
[0041] Mix ferric chloride hydrate, ferrous chloride hydrate and isopropyl alcohol together and stir evenly;
[0042] Heat to 50℃±5℃, slowly drop concentrated ammonia solution, and stir to react for 10-30 minutes;
[0043] After the reaction is completed, the reaction solution is placed at 0-10°C for 4-6 hours;
[0044] After washing with methanol, adding a methanol solution in which oleic acid is dissolved, and stirring for 2-5 hours to obtain the magnetic particles;
[0045] The magnetic particles were washed again with methanol and dispersed in hexane.
[0046] In at least one embodiment of the present application, forming magnetic particles comprises:
[0047] Mix ferric chloride, ferrous chloride, hydrochloric acid and deionized water together and stir evenly to obtain an iron ion mixture;
[0048] Under the condition of introducing protective gas and continuously stirring at 80°C ± 5°C, the iron ion mixture is added dropwise to the sodium hydroxide solution, and the reaction is continued for 20 to 40 minutes after the iron ion mixture is completely added;
[0049] After the reaction is completed, the mixture is cooled to room temperature and washed with anhydrous ethanol and deionized water, and then dried to obtain the magnetic particles.
[0050] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the technical solutions in the embodiments of the present application or related technologies, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0052] Figures 1 and 2 show the structures of two polymer microspheres in the related art;
[0053] FIG3 shows a structure of a polymer microsphere provided in an embodiment of the present application;
[0054] FIG4 is a flow chart of a method for preparing polymer microspheres provided in an embodiment of the present application;
[0055] Figures 5 to 7 are diagrams illustrating the preparation principle of the first type of polymer microspheres provided in the examples of the present application;
[0056] 8 and 9 are diagrams illustrating the preparation principle of the second type of polymer microspheres provided in the examples of the present application;
[0057] Figures 10-11 are diagrams illustrating the preparation principle of the third type of polymer microspheres provided in the examples of the present application;
[0058] 12-15 are comparative diagrams illustrating the magnetic adsorption effect of the polymer microspheres provided in the embodiments of the present application after heating. Specific embodiments
[0059] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0060] Unless the context requires otherwise, throughout the specification and claims, the term "including" is to be interpreted as having an open, inclusive meaning, that is, "including, but not limited to". In the description of the specification, the terms "one embodiment", "some embodiments", "exemplary embodiments", "example", "specific example" or "some examples" are intended to indicate that specific features, structures, materials or characteristics associated with the embodiment or example are included in at least one embodiment or example of the present application. The schematic representation of the above terms does not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials or characteristics may be included in any one or more embodiments or examples in any appropriate manner.
[0061] In the embodiments of the present application, words such as "first" and "second" are used to indicate parts of identical or similar items with substantially the same functions and effects only for the purpose of clearly describing the technical solutions of the embodiments of the present application, and shall not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.
[0062] Magnetic nano- or micro-composites, such as magnetic beads, have attracted widespread attention due to their potential applications in biotechnology and biomedicine. In the biological field, magnetic beads are generally differentiated based on their intended use, with variations in size, surface modification, storage methods, and synthesis methods. Current applications of magnetic beads in the biological field include nucleic acid extraction, chemiluminescence, cell sorting, protein purification, biocatalysis, fluorescent labeling, magnetic resonance imaging, and magnetic hyperthermia. However, due to size limitations and thermal stability limitations, magnetic beads in related technologies suffer from poor magnetic response or unstable magnetic adsorption in practical applications.
[0063] For example, one situation in the related art is: magnetic particles are embedded in polymer microspheres, with the magnetic particles as the core structure of the polymer microspheres and the high molecular polymer as the shell structure; however, the magnetic polymer microspheres formed in this way, as shown in FIG1 , when the magnetic particles are embedded as the core structure H in the polymer microspheres (shell structure K), the overall content of the magnetic particles is low due to the size limitation of the polymer microspheres, and the magnetic response effect is poor; it should be noted that the size limitation of the polymer microspheres refers to: in the polymerization process in the related art, the size range of the polymer microspheres is usually from hundreds of nanometers to several micrometers, while the magnetic particles are generally around 10 nm, which makes the overall content of the magnetic particles in the polymer microspheres very low;
[0064] For example, in another related art scenario, as shown in Figure 2, polymer microspheres serve as the core structure H. At least one layer of magnetic particles is wrapped around the polymer microspheres as the shell structure K. A modified layer X is then formed on the magnetic particles serving as the shell structure K to protect the magnetic particles. However, in this type of structure, after cyclic heating, the interfaces of the magnetic particles may fuse, causing changes in coercivity and resulting in unstable magnetic response and magnetic adsorption.
[0065] The coercive force refers to the fact that after a magnetic material is saturated magnetized, when the external magnetic field returns to zero, its magnetic induction intensity does not return to zero. Only by adding a magnetic field of a certain magnitude in the opposite direction of the original magnetizing field can the magnetic induction intensity return to zero. This magnetic field is called the coercive magnetic field, also known as the coercive force.
[0066] Based on this, the embodiment of the present application provides a kind of polymer microsphere, wherein, the polymer microsphere comprises a core body and a shell that wraps the core body; the core body comprises at least two magnetic particles and a dispersion located between two adjacent magnetic particles; the shell comprises a shell body and a modified layer, the modified layer is located on the side of the shell body away from the magnetic particles, and the modified layer is located on the side of the shell body away from the magnetic particles; wherein, the materials of the dispersion, the shell body and the modified layer are the same. The embodiment of the present application synthesizes the above-mentioned polymer microspheres by in situ polymerization, the core structure in the polymer microsphere comprises magnetic particles and a dispersion, when the number of magnetic particles in the core structure is two or more, the dispersion helps to separate the interfaces between the magnetic particles, and avoids the mutual melting of the interfaces of the magnetic particles in the core structure under thermal cycling conditions; the shell structure of the polymer microsphere comprises a shell body and a modified layer, the shell body plays the role of protecting the core structure, and the modified layer makes the shell surface have specific functional groups; by setting the materials of the dispersion, the shell body and the modified layer to be the same, the setting of the shell structure can be greatly simplified, the preparation process of the polymer microsphere can be simplified, and its quality can be ensured while reducing costs.
[0067] The embodiments of the present application will be described below with reference to the accompanying drawings.
[0068] An embodiment of the present application provides a polymer microsphere, as shown in FIG3 , wherein the polymer microsphere includes a core H and a shell K encapsulating the core H;
[0069] The core H includes at least two magnetic particles HC and a dispersion HF located between the two adjacent magnetic particles HC; the shell K includes a shell body KB and a modification layer KX, and the shell body KB is located on the side of the modification layer KX away from the magnetic particles HC; wherein the dispersion HF, the shell body KB and the modification layer KX are made of the same material.
[0070] The material of the magnetic particles HC is not limited here. For example, the material of the magnetic particles HC may include a magnetic material;
[0071] For example, the magnetic material can be an alloy material, and the main varieties of alloys include AlNi(Co), FeCr(Co), FeCrMo, FeAlC, FeCo(V)(W), Re-Co (Re represents a rare earth element), Re-Fe, AlNi(Co), FeCrCo, FeCrCo, PtCo, MnAlC, CuNiFe and AlMnAg;
[0072] For another example, the magnetic material may include a ferrite material, the main component of which is MO·6Fe2O3, where M represents a composite component such as Ba, Sr, Pb or SrCa, LaCa, etc.;
[0073] For another example, the magnetic material may be an intermetallic compound, mainly represented by MnBi.
[0074] The magnetic particles HC provided in the embodiments of the present application are described by taking as an example an example in which the main components thereof are iron oxide (Fe 3 O 4 ) and / or ferrous oxide (Fe 2 O 3 ).
[0075] In an exemplary embodiment, the dispersion HF is used to disperse and isolate the magnetic particles HC to prevent interfacial melting between two adjacent magnetic particles HC under thermal cycling conditions.
[0076] In at least one embodiment of the present application, the dispersion HF is configured to be able to wrap at least a portion of the surface of the magnetic particles HC. The dispersion HF is configured to be able to wrap at least a portion of the surface of the magnetic particles HC, including but not limited to the following:
[0077] First, all magnetic particles HC are individually coated by the dispersion HF. In this case, the dispersion HF is configured to coat all surfaces of the magnetic particles HC.
[0078] Second, for all magnetic particles HC, there are two or more magnetic particles HC that are simultaneously wrapped together by the dispersion HF. In this case, the dispersion HF is configured to wrap part of the surface of the magnetic particles HC.
[0079] The third type, all magnetic particles HC include a first part and a second part. The magnetic particles HC in the first part are individually wrapped by the dispersion HF, and the dispersion HF is configured to wrap all surfaces of the magnetic particles HC in the first part; in the second part of the magnetic particles HC, two or more magnetic particles HC are simultaneously wrapped together by the dispersion HF, and the dispersion HF is configured to wrap part of the surface of the magnetic particles HC.
[0080] For example, the housing body KB and the finishing layer KX are an integrated structure, which means that they are made of the same material and in the same manufacturing process. It is understood that the housing body KB and the finishing layer KX can be considered as a whole structure.
[0081] Exemplarily, the dispersion HF, the housing body KB and the finishing layer KX are an integrated structure.
[0082] In an exemplary embodiment, the modification layer HX contains functional groups, such as at least one of amino, carboxyl, hydroxyl, and silanol groups, so that the surface of the polymer microspheres carries at least one of these functional groups.
[0083] In the embodiment of the present application, since the dispersion HF, the shell body KB and the modified layer KX are made of the same material, the dispersion HF and the shell body KB also contain functional groups, such as at least one of amino, carboxyl, hydroxyl and silanol groups.
[0084] In an exemplary embodiment, the materials of the dispersion HF, the housing body KB, and the finishing layer KX can be copolymers, also known as interpolymers. Copolymers are polymers obtained through addition polymerization of two or more different monomers. Depending on the arrangement of the monomers in the copolymer molecular chain, copolymers can be classified as random copolymers, alternating copolymers, block copolymers, and graft copolymers. The present application does not limit the type of copolymer.
[0085] In an exemplary embodiment, the materials of the dispersion HF, the housing body KB, and the modifying layer KX may be polycondensates, wherein a polymer formed by a condensation polymerization reaction of two monomers containing different groups is called a polycondensate.
[0086] Copolymers are polymers produced by addition polymerization, while condensation polymers are polymers produced by condensation polymerization. The reaction mechanisms of the two are different. The specific differences between addition polymerization and condensation polymerization can be found in the relevant literature and will not be elaborated here.
[0087] In the embodiments of the present application, the polymer microspheres are synthesized by in-situ polymerization. The core structure H in the polymer microspheres includes magnetic particles HC and a dispersion HF. When the number of magnetic particles HC in the core structure H is two or more, the dispersion HF helps to separate the interfaces between the magnetic particles HC, thereby preventing the interfaces of the magnetic particles HC in the core structure H from melting each other under thermal cycling conditions. The shell structure K of the polymer microspheres includes a shell body KB and a modification layer KX. The shell body KB protects the core structure H, and the modification layer KX imparts specific functional groups to the surface of the shell K. By making the dispersion HF, the shell body KB, and the modification layer KX the same material, the configuration of the shell structure K and the preparation process of the polymer microspheres can be greatly simplified, thereby ensuring their quality while reducing costs.
[0088] In at least one embodiment of the present application, the polymer microspheres can be used for the extraction of nucleic acids, wherein the nucleic acids include ribonucleic acid (RNA for short) and deoxyribonucleic acid (DNA for short).
[0089] In at least one embodiment of the present application, the polymer microspheres can be used for extraction and purification of antibody proteins.
[0090] In at least one embodiment of the present application, the materials of the dispersion HF, the shell body KB and the modification layer KX all include a polymer formed by at least one first monomer and at least one second monomer; the molar ratio of the first monomer to the second monomer ranges from 0.1 to 10.
[0091] For example, the first monomer can be used as a bulk monomer to provide a matrix for the polymer microspheres; the second monomer can be used as a functional monomer to provide functional groups, including but not limited to at least one of amino, carboxyl, hydroxyl, and silanol groups.
[0092] In at least one embodiment of the present application, the second monomer and the modified layer both include at least one group selected from the group consisting of amino, carboxyl, hydroxyl, and silanol.
[0093] There is no limitation on the number of types of the first monomer and the number of types of the second monomer. For example, in order to facilitate the polymerization reaction and simplify the polymerization preparation process, the materials of the dispersion HF, the shell body KB and the modification layer KX can all include a polymer formed by a first monomer and at least one second monomer.
[0094] The molar ratio of the first monomer to the second monomer ranges from 0.1 to 10, where molar amount is actually short for molar mass. The mass per mole of a substance is called "molar mass."
[0095] Illustratively, the molar ratio of the first monomer to the second monomer can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.5, 1.8, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, or 9.5.
[0096] When the molar ratio of the first monomer to the second monomer is greater than 1, the molar mass proportion of the first monomer is greater than the molar mass proportion of the second monomer.
[0097] In at least one embodiment of the present application, the molar amount of the second monomer is less than the molar amount of the first monomer.
[0098] In the embodiments of the present application, by setting the molar amount of the second monomer to be less than the molar amount of the first monomer, the content of the functional groups provided by the functional monomer can be effectively controlled and adjusted. On the one hand, the problem of polymer microsphere agglomeration caused by excessive concentration of functional groups can be effectively reduced; on the other hand, the problem of chemical reaction between two adjacent functional groups on the same polymer microsphere, which causes the failure of the functional groups on the surface of the polymer microsphere, can be avoided to a large extent; the storage stability of the polymer microspheres is improved and the storage period of the polymer microspheres is delayed.
[0099] In at least one embodiment of the present application, the first monomer includes at least one of styrene, butadiene, pentadiene, isoprene, methyl acrylate, acrylonitrile, methyl methacrylate, and tetraethyl orthosilicate;
[0100] The second monomer includes at least one of methacrylic acid, ethyleneimine, hydroxyethylpropylene, tetraethyl orthosilicate, vinylsiloxane, N-(4-carboxyphenyl)maleimide, aminopropyltriethoxysilane, and glyoxal.
[0101] In this specification, "at least one of A, B, and C" refers to one or more of A, B, and C. "Multiple" refers to two or more. Similar descriptions elsewhere have similar meanings and are not repeated here.
[0102] In at least one embodiment of the present application, the ratio of the mass of the magnetic particle HC to the sum of the masses of the first monomer and the second monomer is in the range of 0.5-3.
[0103] The ratio of the mass of the magnetic particle HC to the sum of the masses of the first monomer and the second monomer can be understood as the ratio of the mass of the magnetic particle HC to the sum of the masses of the shell K and the dispersion HF.
[0104] In an exemplary embodiment, in order to ensure that the polymer microspheres have stable and accurate magnetic responsiveness, there are requirements for the quality of the magnetic particles HC.
[0105] For example, the ratio of the mass of the magnetic particles HC to the sum of the masses of the first and second monomers can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.2, 1.4, 1.5, 1.8, 2.0, 2.3, 2.5, 2.8, or 2.9. A larger value of this ratio indicates a higher proportion of the magnetic particles HC in the polymer microspheres and a better magnetic response of the polymer microspheres.
[0106] It should be noted that the greater the ratio of the mass of the magnetic particle HC to the sum of the masses of the first and second monomers, the thicker the shell K in the polymer microsphere. When the ratio of the mass of the magnetic particle HC to the sum of the masses of the first and second monomers is greater than 3, the magnetic responsiveness of the polymer microsphere may decrease, thereby reducing the detection accuracy and efficiency of the polymer microspheres in the biomedical field. When the ratio of the mass of the magnetic particle HC to the sum of the masses of the first and second monomers is less than 0.5, the thickness of the shell K in the polymer microsphere is too thin. Under external forces, the shell K is insufficient to protect the magnetic particle HC in the core structure H, and the shell structure K is prone to rupture. Under thermal cycling, the shell K is insufficient to reduce the heat received by the magnetic particle HC, and the magnetic particle HC interface is prone to melting, reducing magnetic responsiveness and changing coercivity.
[0107] In at least one embodiment of the present application, the first monomer includes styrene, the second monomer includes methacrylic acid, and the molar ratio of the first monomer to the second monomer ranges from 0.1 to 10.
[0108] Illustratively, the molar ratio of the first monomer to the second monomer can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.5, 1.8, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, or 9.5.
[0109] When the first monomer includes styrene and the second monomer includes methacrylic acid, the copolymer formed by the first monomer and the second monomer is a copolymer of styrene and methacrylic acid. Since the second monomer is methacrylic acid, the surface of the polymer microsphere (modified layer KX) ultimately has carboxyl groups (-COOH).
[0110] When the surface of the polymer microspheres (modification layer KX) carries carboxyl groups (-COOH), the polymer microspheres can be used for DNA extraction and purification.
[0111] In at least one embodiment of the present application, the first monomer includes tetraethyl orthosilicate, the second monomer includes aminopropyltriethoxysilane and glyoxal, the molar ratio of the first monomer to the total amount of monomers ranges from 0.1 to 0.8, the molar ratio of aminopropyltriethoxysilane to the total amount of monomers in the second monomer ranges from 0.1 to 0.4, and the molar ratio of glyoxal to the total amount of monomers in the second monomer ranges from 0.1 to 0.5. The above-mentioned total amount of monomers refers to the total amount of tetraethyl orthosilicate, aminopropyltriethoxysilane, and glyoxal.
[0112] For example, the molar ratio of the first monomer to the total amount of monomers may be 0.2, 0.3, 0.4, 0.5, 0.6, or 0.7;
[0113] For example, the molar ratio of aminopropyltriethoxysilane to the total amount of monomers in the second monomer is 0.2, 0.25, 0.3, or 0.35;
[0114] Illustratively, the molar ratio of glyoxal in the second monomer to the total amount of monomers is 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, or 0.45.
[0115] In exemplary embodiments, a molar amount of the first monomer may be greater than a molar amount of aminopropyltriethoxysilane in the second monomer.
[0116] In exemplary embodiments, the molar amount of the first monomer may be greater than the molar amount of glyoxal in the second monomer.
[0117] In exemplary embodiments, the molar amount of the first monomer may be greater than the total molar amount of aminopropyltriethoxysilane and glyoxal in the second monomer.
[0118] In the case where the first monomer comprises tetraethyl orthosilicate and the second monomer comprises aminopropyltriethoxysilane and glyoxal, the condensation polymer of the first and second monomers is a condensation polymer of tetraethyl orthosilicate, aminopropyltriethoxysilane, and glyoxal. Because the second monomer comprises aminopropyltriethoxysilane, the siloxy groups in the formed condensation polymer generate abundant silanol (-Si-OH) groups upon hydrolysis, resulting in the surface of the polymer microspheres (modified layer KX) being coated with silanol (-Si-OH) groups.
[0119] When the surface of the polymer microspheres (modification layer KX) carries silanol groups (-Si-OH), the polymer microspheres can be used for RNA extraction and purification.
[0120] In at least one embodiment of the present application, the first monomer includes styrene, the second monomer includes ethyleneimine, the molar ratio of the first monomer to the total monomer amount is in a range of 0.1 to 0.6, and the molar ratio of the second monomer to the total monomer amount is in a range of 0.4 to 0.9. The total monomer amount refers to the total molar amount of styrene and ethyleneimine.
[0121] For example, the molar ratio of the first monomer to the total amount of monomers may be 0.2, 0.3, 0.4, or 0.5;
[0122] For example, the molar ratio of the second monomer to the total amount of monomers may be 0.5, 0.6, 0.7, or 0.8;
[0123] For example, the molar amount of the first monomer may be greater than the molar amount of the second monomer.
[0124] Among them, when the first monomer includes styrene and the second monomer includes ethyleneimine, the copolymer of the first monomer and the second monomer is a copolymer of styrene and ethyleneimine; since the copolymer includes imine groups, the surface of the polymer microspheres (modified layer KX) ultimately has amino groups (-NH2).
[0125] When the surface of the polymer microspheres (modification layer KX) carries amino groups (-NH2), the polymer microspheres can be used for the extraction and purification of antibody proteins.
[0126] In at least one embodiment of the present application, as shown in FIG3 , the distance D between the magnetic particle HC and the modified layer KX in the direction from the geometric center of the polymer microsphere to the modified layer KX ranges from 10 nm to 500 nm.
[0127] Illustratively, the distance D between the magnetic particle HC and the modified layer KX in the direction from the geometric center of the polymer microsphere to the modified layer KX can be 15 nm, 30 nm, 50 nm, 100 nm, 150 nm, 180 nm, 200 nm, 300 nm, 350 nm, 280 nm, 400 nm, 450 nm, or 480 nm.
[0128] In at least one embodiment of the present application, the magnetic particles HC include one or more of iron oxide, cobalt oxide, and nickel oxide, and the size of the magnetic particles HC ranges from 8 nm to 15 nm.
[0129] For example, the size of the magnetic particles may be 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, or 14 nm.
[0130] For example, the magnetic particles may include ferrite materials, the main component of which is MO·6Fe2O3, where M represents Ba, Sr, Pb or a composite component such as SrCa, LaCa, etc.
[0131] For example, the magnetic particles may include at least one of ferroferric oxide and ferrous oxide.
[0132] In the embodiment of the present application, since the size range of the magnetic particles is set to 8nm to 15nm, in order to improve the smoothness of the surface of the polymer microspheres, avoid the appearance of a concave-convex structure on the surface of the polymer microspheres after the shell K covers the core H, and avoid the shell K of the polymer microspheres from breaking under the action of external force, the minimum distance D between the magnetic particles HC and the modified layer KX in the direction from the geometric center of the polymer microspheres to the modified layer KX is set to be similar to the size of the magnetic particles HC, that is, the minimum distance D between the magnetic particles HC and the modified layer KX in the direction from the geometric center of the polymer microspheres to the modified layer KX is 10nm; thereby improving the smoothness of the surface of the polymer microspheres and reducing the probability of the shell K of the polymer microspheres breaking under the action of external force; in addition, when the distance D between the magnetic particles HC and the modified layer KX in the direction from the geometric center of the polymer microspheres to the modified layer KX is greater than 500nm, the content of the magnetic particles HC in the polymer microspheres decreases and the magnetic response effect deteriorates.
[0133] In at least one embodiment of the present application, the size of the polymer microspheres ranges from 100 nm to 5 μm.
[0134] For example, the size of the polymer microspheres can be 200 nm, 300 nm, 500 nm, 800 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or 4.5 μm.
[0135] It should be noted that the dimensions in this specification are all average values, and fluctuations of 3% to 5% within the range around the average value fall within the scope of protection of this application.
[0136] Next, the preparation method of polymer microspheres is introduced.
[0137] In practical applications, magnetic microspheres are typically prepared by first preparing magnetic particles and then coating them with a polymer or silica layer. Related art methods for preparing magnetic particles include solvent-gel methods, coprecipitation methods, hydrothermal methods, and high-temperature organic phase thermal decomposition methods. The detailed procedures of these methods can be found in related art and will not be detailed here.
[0138] Due to size limitations and thermal stability limitations, magnetic microspheres prepared by the preparation methods in related technologies have problems such as poor magnetic response or unstable magnetic adsorption in practical applications.
[0139] Based on this, an embodiment of the present application provides a method for preparing polymer microspheres, which is applied to prepare the polymer microspheres as described above, and the method comprises:
[0140] S801, forming magnetic particles HC;
[0141] Illustratively, the magnetic particles HC include one or more of iron oxide, cobalt oxide, and nickel oxide, and the size of the magnetic particles HC ranges from 8 nm to 15 nm.
[0142] For example, the magnetic particles HC may comprise γ-Fe 3 O 4 nanoparticles.
[0143] S802. Magnetic particles HC, at least one first monomer, and at least one second monomer are mixed together, and polymer microspheres are formed in one step by in-situ polymerization; wherein the polymer microspheres include a core H and a shell K encapsulating the core H; the core H includes at least two magnetic particles HC and a dispersion HF located between the two adjacent magnetic particles HC; the shell K includes a shell body KB and a modification layer KX, and the modification layer KX is located on a side of the shell body KB away from the magnetic particles HC; wherein the dispersion HF, the shell body KB, and the modification layer KX are made of the same material and all include a polymer formed by at least one first monomer and at least one second monomer.
[0144] It should be noted that the above step S802 is carried out during continuous stirring to promote good dispersion of the magnetic particles HC. The stirring includes mechanical stirring and ultrasonic treatment, thereby further improving the dispersion effect of the magnetic particles HC in the system, so as to facilitate obtaining magnetic particles HC individually wrapped by the dispersion HF.
[0145] In an exemplary embodiment, the dispersion HF is used to disperse and isolate the magnetic particles HC to prevent interfacial melting between two adjacent magnetic particles HC under thermal cycling conditions.
[0146] In at least one embodiment of the present application, the dispersion HF covers at least a portion of the surface of the magnetic particles HC. The dispersion HF is configured to be able to wrap at least a portion of the surface of the magnetic particles HC, including but not limited to the following:
[0147] First, all magnetic particles HC are individually coated by the dispersion HF. In this case, the dispersion HF is configured to coat all surfaces of the magnetic particles HC.
[0148] Second, for all magnetic particles HC, there are two or more magnetic particles HC that are simultaneously wrapped together by the dispersion HF. In this case, the dispersion HF is configured to wrap part of the surface of the magnetic particles HC.
[0149] The third type, all magnetic particles HC include a first part and a second part. The magnetic particles HC in the first part are individually wrapped by the dispersion HF, and the dispersion HF is configured to wrap all surfaces of the magnetic particles HC in the first part; in the second part of the magnetic particles HC, two or more magnetic particles HC are simultaneously wrapped together by the dispersion HF, and the dispersion HF is configured to wrap part of the surface of the magnetic particles HC.
[0150] In an exemplary embodiment, the modification layer HX contains functional groups, such as at least one of amino, carboxyl, hydroxyl, and silanol groups, so that the surface of the polymer microspheres carries at least one of these functional groups.
[0151] In the embodiment of the present application, since the dispersion HF, the shell body KB and the modified layer KX are made of the same material, the dispersion HF and the shell body KB also contain functional groups, such as at least one of amino, carboxyl, hydroxyl and silanol groups.
[0152] In the in-situ polymerization method, the reactive monomers (first and second monomers) and the catalyst are added to the dispersed phase (magnetic particle dispersion) and mixed. Because the reactive monomers are soluble in the reaction solvent system, while the polymer is insoluble in the overall system, the polymerization reaction occurs on the magnetic particles HC. The reaction begins with prepolymerization of the reactive monomers, followed by polymerization of the prepolymer. As the prepolymer gradually increases in size, it deposits on the surface of the magnetic particles HC and further coats them, forming the polymer microsphere dispersion HF, the shell body KB, and the modified layer KX.
[0153] In the embodiments of the present application, polymer microspheres are synthesized by in-situ polymerization. The core structure H in the polymer microspheres includes magnetic particles HC and a dispersion HF. When the number of magnetic particles HC in the core structure H is two or more, the dispersion HF helps to separate the interfaces between the magnetic particles HC, thereby preventing the interfaces of the magnetic particles HC in the core structure H from melting each other under thermal cycling conditions. The shell structure K of the polymer microspheres includes a shell body KB and a modification layer KX. The shell body KB protects the core structure H, and the modification layer KX imparts specific functional groups to the surface of the shell K. By arranging the materials of the dispersion HF, the shell body KB, and the modification layer KX to be the same, the configuration of the shell structure K and the preparation process of the polymer microspheres can be greatly simplified, thereby ensuring their quality while reducing costs.
[0154] In at least one embodiment of the present application, step S802, mixing the magnetic particles, at least one first monomer, and at least one second monomer to form polymer microspheres in one step by in-situ polymerization, includes two cases:
[0155] In the first case, the in-situ copolymerization method is used: S8021, magnetic particles HC, a first monomer and a second monomer are mixed together, and polymer microspheres are formed in one step by in-situ polymerization;
[0156] In at least one embodiment of the present application, the first monomer includes styrene and the second monomer includes methacrylic acid; in this case, step S8021 includes:
[0157] S8021A, dispersing magnetic particles HC in anhydrous ethanol to obtain a suspension of magnetic particles HC;
[0158] For example, 0.23 g of Fe2O3 nanoparticles and 40 mL of anhydrous ethanol were transferred to a four-necked flask, and the mixture was ultrasonically treated for 5 minutes. In practical applications, the ultrasonic time can be appropriately adjusted according to the power of the ultrasonic equipment, such as ultrasonication for 10 minutes or 15 minutes, to help disperse the Fe2O3 nanoparticles.
[0159] S8021B, adding polyvinyl pyrrolidone (PVP), an initiator, and a second monomer to a suspension of magnetic particles HC, introducing a protective gas; after stirring evenly, adding a first monomer, and continuously stirring and reacting at a first preset temperature for 2 to 6 hours; the first monomer includes styrene, and the second monomer includes methacrylic acid;
[0160] Stirring includes mechanical stirring and ultrasonic treatment. Since ultrasonic treatment may generate heat rapidly, the above-mentioned continuous stirring reaction for 2 to 6 hours includes continuous mechanical stirring, and mechanical stirring and ultrasonic treatment are performed alternately, but does not include continuous ultrasonic treatment.
[0161] Among them, the addition of polyvinyl pyrrolidone (PVP) helps to increase the molecular weight of the polymer. Ethanol itself has poor solubility in the copolymer. The addition of polyvinyl pyrrolidone (PVP) helps the copolymer to dissolve better in the ethanol solution, so that the reaction can continue to obtain a higher molecular weight. The role of adding PVP in the preparation method later is similar to that here and will not be repeated here.
[0162] Exemplarily, the first preset temperature may be 80±5°C, for example, 80±2°C.
[0163] For example, the shielding gas may be an inert gas, such as nitrogen (N2).
[0164] For example, the initiator may include dibenzoyl peroxide (BPO); the molar ratio of the initiator to the total reactive monomers ranges from 0.01 to 0.1. For example, the molar ratio of the initiator to the total reactive monomers may be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, or 0.09.
[0165] Illustratively, the molar ratio of the first monomer to the second monomer ranges from 0.1 to 10. For example, the molar ratio of the first monomer to the second monomer can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.5, 1.8, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, or 9.5.
[0166] For example, 0.25 g of polyvinylpyrrolidone (PVP), 0.025 g of dibenzoyl peroxide (BPO), and 0.5 mL of redistilled methacrylic acid (AA) are added to a suspension of magnetic particles HC; after uniform stirring (ultrasonic dispersion), and nitrogen protection, the mixture is mechanically stirred at 30°C for 1 hour, and then 2 mL of redistilled styrene is added to the mixture; mechanical stirring is continued at 78°C for 4 hours, accompanied by intermittent ultrasonic treatment during the reaction.
[0167] S8021C, after the reaction solution is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain polymer microspheres.
[0168] For example, after the reaction solution cools to room temperature, the resulting product is magnetically separated, washed several times with ethanol and water, and dried in a vacuum oven at 40°C for 12 hours to obtain Fe2O3 / PS-PAA polymer microspheres. The magnetic particles HC are made of Fe2O3; the dispersion HF, the shell KB, and the modification layer KX are all made of a copolymer of styrene and methacrylic acid (PS-PAA).
[0169] When the first monomer includes styrene, the second monomer includes methacrylic acid, and the initiator includes dibenzoyl peroxide (BPO), the reaction mechanism is shown in Figures 5 to 7;
[0170] In Figure 5, dibenzoyl oxide (BPO) undergoes thermal decomposition under heating conditions to generate free radicals PHCOO·, which further react to generate free radicals PH· and CO2;
[0171] In Figure 6, the free radical PH· polymerizes with methacrylic acid and styrene in sequence to obtain a prepolymer Here, PH represents phenyl.
[0172] In Figure 7, the prepolymer is deposited on the iron oxide nanoparticles and further polymerized to obtain the dispersion HF, the shell body KB and the modified layer KX; at this time, the surface of the polymer microspheres has carboxyl groups (-COOH).
[0173] The structural formula of the copolymer of styrene and methacrylic acid (PS-PAA) is as follows:
[0174] Wherein, x and y are both positive integers.
[0175] In at least one embodiment of the present application, the first monomer includes styrene and the second monomer includes ethyleneimine; in this case, step S8021 includes:
[0176] S8021a, dispersing magnetic particles HC in anhydrous ethanol to obtain a suspension of magnetic particles;
[0177] For example, 5 g of Fe3O4 nanoparticles and 10 mL of anhydrous ethanol are transferred to a four-necked flask, and the mixture is ultrasonically treated for 5 minutes. In practical applications, the ultrasonic time can be appropriately adjusted according to the power of the ultrasonic equipment, such as 10 minutes or 15 minutes, to help disperse the Fe3O4 nanoparticles.
[0178] S8021b, adding polyvinyl pyrrolidone (PVP), an initiator, a first monomer, and a second monomer to a suspension of magnetic particles HC; and continuously stirring the reaction for 2 to 4 hours under vacuum and a second preset temperature; the first monomer includes styrene, and the second monomer includes ethyleneimine;
[0179] Stirring includes mechanical stirring and ultrasonic treatment. Since ultrasonic treatment may generate heat rapidly, the above-mentioned continuous stirring reaction for 2 to 4 hours includes continuous mechanical stirring and alternating mechanical stirring and ultrasonic treatment, and does not include continuous ultrasonic treatment.
[0180] Exemplarily, the second preset temperature may be 130±10°C, for example, 130±5°C, 130±2°C.
[0181] For example, the free radical initiator may include dibenzoyl peroxide (BPO); the molar ratio of the free radical initiator to the total reactive monomer is in a range of 0.01 to 0.1. For example, the molar ratio of the free radical initiator to the total reactive monomer may be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, or 0.09.
[0182] For example, the molar ratio of the first monomer to the total monomer amount is in the range of 0.1 to 0.6, and the molar ratio of the second monomer to the total monomer amount is in the range of 0.4 to 0.9, wherein the total monomer amount refers to the total molar amount of styrene and ethyleneimine.
[0183] For example, 0.25 g polyvinylpyrrolidone (PVP), 0.025 g dibenzoyl peroxide (BPO), 5.4 g ethyleneimine and 15 mL redistilled styrene are added to the suspension of magnetic particles HC; the suspension is evacuated to 2 bar, heated to 135±1° C. and mechanically stirred for 3 hours.
[0184] S8021c, after the reaction solution is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain polymer microspheres.
[0185] After the reaction is completed, cool to room temperature, transfer the reaction mixture to a plastic container, place it on a magnetic rack, remove the supernatant, and then rinse twice with 200 mL of deionized water until the pH of the rinse solution reaches approximately 7. Rinse twice with anhydrous ethanol and dry. This yields Fe₃O₄ / PS-PEI polymer microspheres. The magnetic particles HC are made of Fe₃O₄; the dispersion HF, the shell KB, and the modification layer KX are all made of a copolymer of styrene and ethyleneimine (PS-PEI).
[0186] When the first monomer includes styrene, the second monomer includes ethyleneimine, and the initiator includes dibenzoyl peroxide (BPO), the reaction mechanism is shown in Figures 5, 8, and 9;
[0187] In Figure 5, dibenzoyl oxide (BPO) undergoes thermal decomposition under heating conditions to generate free radicals PHCOO·, which further react to generate free radicals PH· and CO2;
[0188] In Figure 8, the free radical PH· polymerizes with styrene and ethyleneimine in sequence to form a prepolymer
[0189] In Figure 9, the prepolymer is deposited on the iron oxide nanoparticles and further polymerized to obtain the dispersion HF, the shell body KB and the modified layer KX; at this time, the surface of the polymer microspheres has amino groups (-NH2).
[0190] The structural formula of the copolymer of styrene and ethyleneimine (PS-PEI) is as follows:
[0191] Wherein, x and y are both positive integers.
[0192] The above-mentioned in situ copolymerization preparation method provided in the embodiments of the present application can reduce the process flow, reduce raw material loss, and thus further reduce costs. By controlling the molar concentration ratio of the bulk monomer (first monomer) and the functional monomer (second monomer) in the copolymer, the surface group content of the polymer microspheres can be adjusted, thereby reducing the problem of agglomeration between polymer microspheres caused by excessively high group density.
[0193] In the second case, the in-situ polycondensation method is used:
[0194] S8022. Mix the magnetic particles, a first monomer, and two second monomers together, and form polymer microspheres in one step by in-situ polymerization.
[0195] In at least one embodiment of the present application, the first monomer includes tetraethyl orthosilicate, and the second monomer includes aminopropyltriethoxysilane and glyoxal. In this case, step S8022 includes:
[0196] S8022A, dispersing the first monomer in anhydrous ethanol;
[0197] For example, 15 mL of tetraethyl orthosilicate was added to a reaction bottle containing 50 mL of anhydrous ethanol and magnetically stirred for 15 minutes;
[0198] S8022B, dispersing the magnetic particles HC in an aqueous solution containing polyvinylpyrrolidone (PVP) to obtain a suspension of the magnetic particles HC;
[0199] For example, 22.5 g of ferrosoferric oxide nanoparticles were dispersed in 50 mL of polyvinylpyrrolidone (PVP) solution and stirred (magnetic stirring, mechanical stirring or ultrasonic dispersion) for 15 minutes;
[0200] S8022C, adding a suspension of magnetic particles HC to anhydrous ethanol in which a first monomer is dispersed, then adding two second monomers and aqueous ammonia, stirring evenly, and reacting at a third preset temperature for 1 to 3 hours; wherein the first monomer comprises tetraethyl orthosilicate, and the second monomer comprises aminopropyltriethoxysilane and glyoxal;
[0201] Exemplarily, the third preset temperature may be 80±5°C, for example, 80±2°C.
[0202] The molar ratio of the first monomer to the total amount of monomers is in the range of 0.1 to 0.8, the molar ratio of the aminopropyltriethoxysilane in the second monomer to the total amount of monomers is in the range of 0.1 to 0.4, and the molar ratio of the glyoxal in the second monomer to the total amount of monomers is in the range of 0.1 to 0.5. The total amount of monomers mentioned above refers to the total amount of tetraethyl orthosilicate, aminopropyltriethoxysilane, and glyoxal.
[0203] For example, a ferroferric oxide dispersion is added to a tetraethyl orthosilicate solution, and then 15 mL of aminopropyltriethoxysilane, 15 mL of adipaldehyde, and 50 mL of 5% ammonia water are added to the mixture. After stirring for 10 minutes, the reaction solution is heated to 80°C and the reaction is continued for 2 hours.
[0204] When the first monomer includes tetraethyl orthosilicate and the second monomer includes aminopropyl triethoxysilane and glyoxal, the condensation polymer of the first and second monomers is a condensation polymer of tetraethyl orthosilicate, aminopropyl triethoxysilane, and glyoxal. Because the second monomer includes aminopropyl triethoxysilane, the siloxy groups in the formed condensation polymer generate abundant silanol (-Si-OH) groups upon hydrolysis, resulting in the surface of the polymer microspheres (modified layer KX) being coated with silanol (-Si-OH) groups.
[0205] S8022D, after the reaction solution is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain polymer microspheres.
[0206] For example, after the reaction is completed, the reaction solution is cooled to room temperature, transferred to a plastic container, placed on a magnetic stand, the supernatant is removed, and then washed with 200 mL of deionized water at least twice until the pH value of the washing solution becomes about 7; washed twice with anhydrous ethanol and dried; polymer microspheres with silanol groups on the surface can be obtained.
[0207] When the first monomer includes tetraethyl orthosilicate and the second monomer includes aminopropyltriethoxysilane and glyoxal, the reaction mechanism is shown in Figures 10 to 12;
[0208] As shown in FIG10 , tetraethyl orthosilicate and aminopropyltriethoxysilane undergo polycondensation under alkaline conditions (ammonia water) to obtain an intermediate product
[0209] As shown in Figure 11, the intermediate product is deposited on the iron oxide nanoparticles and further polymerized, and the dispersion HF, the shell body KB and the modified layer KX are obtained at the same time; because the second monomer includes aminopropyltriethoxysilane, the siloxy groups in the formed condensation polymer generate abundant silanol groups (-Si-OH) under hydrolysis, so the surface of the polymer microspheres (modified layer KX) ultimately carries silanol groups (-Si-OH). The drawings provided in the embodiments of the present application only depict the hydroxyl groups (-OH) on the surface of the polymer microspheres, and do not reflect the silicon atoms (Si).
[0210] Among them, the structural formula of the condensation product of tetraethyl orthosilicate, aminopropyltriethoxysilane and glyoxal is as follows:
[0211] Wherein, x and y are both positive integers.
[0212] The above-mentioned in-situ polycondensation preparation method provided in the embodiments of the present application can reduce the process flow, reduce raw material loss, and thus further reduce costs. By controlling the molar concentration ratio of the bulk monomer (first monomer) and the functional monomer (second monomer) in the polycondensate, the surface group content of the polymer microspheres can be adjusted, thereby reducing the problem of agglomeration between polymer microspheres caused by excessively high group density.
[0213] In the embodiment of the present application, the steps for preparing the magnetic particles HC include the following two methods:
[0214] The first method for preparing magnetic particles HC is as follows:
[0215] Step S801A, mixing ferric chloride hydrate, ferrous chloride hydrate, and isopropyl alcohol together and stirring evenly;
[0216] For example, the specific process can be as follows: 0.5 g of FeCl₃·6H₂O, 50 mL of nitrogen-purged HPLC-grade isopropanol, and a magnetic stirrer are added to a 250 mL two-necked flask. Then, 0.25 g of FeCl₂·4H₂O is added and stirred thoroughly until completely dissolved, resulting in a yellow-orange solution. Isopropanol is used as the reaction solvent.
[0217] Step S801B, heating to 50°C ± 5°C, slowly adding concentrated ammonia solution, stirring and reacting for 10 to 30 minutes;
[0218] For example, the specific process can be as follows: the reaction solution is heated to 50°C, and an excess of concentrated ammonia (<10 mL) is slowly added dropwise to the reaction solution. The reaction is carried out for 15 minutes until the solution turns dark brown, and the mixture is stirred until it cools to room temperature.
[0219] Step S801C: After the reaction is completed, the reaction solution is placed at 0-10°C for 4-6 hours;
[0220] For example, it is placed in an environment of 0-10°C for 5 hours to allow the Fe2O3 magnetic particles to precipitate.
[0221] Step S801D: After washing with methanol, a methanol solution containing oleic acid is added and stirred for 2-5 hours to obtain magnetic particles;
[0222] The precipitated black solid was then washed three times with methanol (to remove residual solvent) and then centrifuged at 10,000 rpm for 5 minutes to precipitate the solid. 10 mM oleic acid was dissolved in 50 ml of methanol and added to the solid, stirring for 3 hours; the oleic acid protects the surface of the iron oxide (Fe2O3) crystals, while the methanol removes excess oleic acid.
[0223] Step S801E: washing again with methanol, and dispersing the obtained magnetic particles in hexane.
[0224] The product was washed with methanol several times and finally dispersed in 50 mL of hexane. Hexane, as a solution dispersant, can effectively disperse the iron oxide coated with oleic acid and further protect the iron oxide crystals.
[0225] The above method prepares an oleic acid-stabilized Fe2O3 magnetic particle suspension. The Fe2O3 magnetic particles have a single crystal structure and an average diameter range of 5 to 15 nm. The reaction yield after drying is approximately 86%.
[0226] The first method for preparing magnetic particles HC involves the following reaction equation: FeCl3+FeCl2+5NH4OH→Fe(OH)3+Fe(OH)2+5NH4Cl
[0227] Fe(OH)3+Fe(OH)2+OH-→Fe2O3+3H2O (control the pH value of the reaction solution at 9-10)
[0228] The magnetic particles HC obtained by the first preparation method are Fe2O3.
[0229] The second preparation method of magnetic particles HC is as follows:
[0230] S801a, mixing ferric chloride, ferrous chloride, hydrochloric acid and deionized water together and stirring evenly to obtain an iron ion mixture;
[0231] For example, the specific process can be as follows: weigh 3.24 g of ferric chloride and 2 g of ferric dichloride tetrahydrate, and place them in a 200 mL conical flask, add 50 mL of deionized water and 6 mL of 1M hydrochloric acid solution (which helps to disperse and stabilize ferric chloride and ferric dichloride), stir and dissolve, then transfer to a volumetric flask, and dilute to 60 mL with deionized water to obtain an iron ion mixture;
[0232] S801b, introducing protective gas and adding the iron ion mixture dropwise to the sodium hydroxide solution at 80°C ± 5°C with continuous stirring, and reacting for 20 to 40 minutes after the iron ion mixture is completely added;
[0233] For example, the specific process can be as follows: take a 250mL double-necked round-bottom reaction flask, a magnetic stirrer, a constant pressure dropping funnel, and a vent plug, add a magnetic stirrer and 100mL of deoxygenated 2Mol sodium hydroxide solution to the reaction flask, stir and mix, take the constant pressure dropping funnel and place it on the vertical bottle mouth of the reaction flask, and pass nitrogen protection. Add the above-mentioned 60mL iron ion mixture to the constant pressure dropping funnel through a syringe, protect with nitrogen during the reaction, heat the sodium hydroxide solution to 80°C, and then control the iron ion mixture to be dripped into the sodium hydroxide solution within 10 minutes to react, and continue to react for 30 minutes after complete dripping. After the reaction is completed, cool to room temperature.
[0234] S801c, after the reaction is completed, the mixture is cooled to room temperature and washed with anhydrous ethanol and deionized water, and dried to obtain magnetic particles.
[0235] For example, the specific process can be as follows: transfer the reaction solution to a plastic container, place it on a magnetic rack, remove the supernatant, then rinse with 200 mL of deionized water five times until the pH of the rinse solution reaches approximately 7. After rinsing with anhydrous ethanol, drying, and weighing, a reaction yield of 91% can be obtained.
[0236] The second method for preparing magnetic particles HC involves the following reaction equation: 2Fe 3+ +Fe 2+ +8OH - →Fe3O4+4H2O
[0237] The magnetic particles HC obtained by the second preparation method are Fe3O4.
[0238] In order to test the performance of the polymer microspheres provided in the examples of the present application, the effects of using different types of polymer microspheres in the nucleic acid extraction process are provided below.
[0239] First, let's compare the performance of different polymer microspheres (also known as magnetic beads) during DNA extraction:
[0240] The following text involves various biological reagents. First, the components of the biological reagents involved in DNA extraction are described.
[0241] DNA extraction reagent system:
[0242] 1. Red blood cell lysis solution, comprising: 5 mM NaCl, 5% Tween 20, 320 mM glucose, 10 mM Tris solution; the pH of the red blood cell lysis solution is about 8, for example, pH = 8.2.
[0243] 2. Lysis buffer, used to lyse cells other than red blood cells, consists of: 3.5M guanidine isothiocyanate (GITC), 0.1% Tween 20, 100mM TE buffer (pH 7.5), 10mM ethylenediaminetetraacetic acid (EDTA), 0.5% sodium lauryl sulfate, and 1% triton X-100. TE buffer is made of Tris and EDTA and is primarily used to dissolve nucleic acids, providing stable storage of DNA and RNA.
[0244] 3. Proteinase K at a concentration of 10 mg / mL, 50 mM Tris solution (pH approximately 8), 5 mM CaCl2, and 20 vol% glycerol;
[0245] 4. Binding fluid, used to promote the binding of polymer microspheres and nucleic acids, its components are:
[0246] 0.5Mol NaCl, 45% isopropanol, 8-15% polyethylene glycol (PEG8000, average molecular weight of about 8000), 100mMol tromethamine (Tris) solution (pH approximately 8.0), 5mMol ethylenediaminetetraacetic acid (EDTA);
[0247] 5. Components of the first cleaning solution: 1X TE buffer, 75% ethanol solution;
[0248] 6. The components of the second cleaning solution are: 1X TE buffer and 80% ethanol solution. Both cleaning solutions are used to clean proteins and salts. The first cleaning solution has a low ethanol concentration and is soluble in nucleic acids, thus avoiding the removal of nucleic acids and reducing the nucleic acid extraction rate.
[0249] Here, 1X TE buffer represents the original concentration of the buffer.
[0250] 7. Elution buffer, used to elute nucleic acids from polymer microspheres (magnetic beads), its components are: 10mMol tris (hydroxymethyl)aminomethane (Tris-HCl), 0.1mMol ethylenediaminetetraacetic acid (EDTA), that is, TE buffer.
[0251] The DNA extraction process consists of two parts: the first part removes the red blood cells, and the second part extracts the DNA;
[0252] The specific process of removing red blood cells in the first part is as follows:
[0253] 1. Take 250 μL of whole blood (bovine whole blood) in a 2 mL centrifuge tube, add 800 μL of red blood cell lysis buffer, and shake thoroughly for 10 seconds to obtain a red, transparent, and clear mixture;
[0254] 2. Centrifuge the mixture at 12000 rpm for 1 minute, remove the supernatant and obtain a white precipitate;
[0255] 3. Add 800 μl of red blood cell lysis buffer to the white precipitate again and shake thoroughly to suspend the precipitate to obtain a mixed solution;
[0256] 4. Centrifuge the mixture at a speed of about 12,000 rpm for 1 minute, remove the supernatant, and obtain a white precipitate for later use.
[0257] The specific process of DNA extraction in the second part is as follows:
[0258] 1. Add 400 μL of lysis buffer to the white precipitate obtained after removing red blood cells, vortex to mix, and react at 65°C for 30 minutes;
[0259] 2. Add 400 μL of isopropanol and vortex to mix.
[0260] 3. Add 20 μL of polymer microspheres (also known as magnetic beads), such as polymer microspheres with silanol (-Si-OH) groups on the surface, polymer microspheres with carboxyl (-COOH) groups on the surface, or polymer microspheres with amino (-NH2) groups on the surface, vortex to mix, let it stand for 5 minutes, and vortex for 3 seconds every 2 minutes;
[0261] 4. Add 600uL of binding solution, vortex and mix, let it stand for 10 minutes, and vortex for 3 seconds every 2 minutes;
[0262] 5. After low-speed centrifugation, place the tube on a magnetic stand and let it stand for 2 minutes. Remove the supernatant.
[0263] 6. Add 600 μL of the first cleaning solution to the product from step 5 above and mix thoroughly by pipetting (use a pipette to aspirate and pipette to mix thoroughly).
[0264] 7. Place on a magnetic stand and let it adsorb for 2 minutes, then remove the supernatant;
[0265] 8. Add 600uL of the second cleaning solution to the product from step 7 above and mix thoroughly by pipetting;
[0266] 9. Place it under magnetic force and let it stand for 2 minutes, then dry it at room temperature until there is no obvious liquid on the surface;
[0267] 10. Add 100uL enzyme-free water or TE buffer and elute at room temperature with shaking for 10 minutes;
[0268] 11. Place the centrifuge tube from step 10 on a magnetic stand and let it stand for 2 minutes. Transfer the supernatant to a new centrifuge tube for the next test. The supernatant is the DNA solution.
[0269] The concentration and purity of DNA extracted using polymer microspheres with silanol (-Si-OH) groups on the surface, polymer microspheres with carboxyl (-COOH) groups on the surface, or polymer microspheres with amino (-NH2) groups on the surface were tested to obtain the data in Table 1.
[0270] Table 1: Comparison of DNA extraction performance of polymer microspheres provided in this application
[0271] Among them, the reference group is the polymer microspheres (magnetic beads) in the related art. It can be seen that the DNA recovery concentration of the polymer microspheres with carboxyl groups (-COOH) on the surface provided in the embodiment of the present application is equivalent to that of the magnetic beads in the related art, and the purity of the extracted DNA is significantly higher than that of the magnetic beads in the related art; it should be noted that each group of data in Table 1 includes 3, and the 3 data are the results of multiple measurements of the same batch of samples.
[0272] The following is a comparison of the performance of different polymer microspheres (also known as magnetic beads) during RNA extraction:
[0273] The following text involves various biological reagents. First, the components of the biological reagents involved in RNA extraction are described.
[0274] RNA extraction reagent system:
[0275] 1. Red blood cell lysis buffer: Its components are the same as those in the red blood cell lysis buffer in the DNA extraction reagent system mentioned above. Please refer to the previous article for details;
[0276] 2. Lysis buffer: 4Mol guanidine isothiocyanate (GITC), 1mMol tris-HCl (Tris-HCl), 0.05% Tween 20, pH 7.5;
[0277] 3. Binding solution: 10% polyethylene glycol (PEG8000, average molecular weight of about 8000), 1Mol NaCl, 20mMol tris-hydroxymethylaminomethane (Tris-HCl), 10mMol ethylenediaminetetraacetic acid (EDTA), 0.05% Tween 20, pH 8;
[0278] 4. Isopropyl alcohol;
[0279] 5. Third cleaning solution: 0.1Mol guanidine isothiocyanate (GITC), 1mMol tris-hydroxymethylaminomethane (Tris-HCl), 0.05% Tween 20, 1Mol NaCl, pH 7.5;
[0280] 6. Fourth cleaning solution: 80% ethanol solution;
[0281] 7. Eluent: enzyme-free water or TE buffer;
[0282] 8. 10X DNase I buffer: 100 mM Tris-HCl, 0.5% Tween 20, 25 mM MgCl2, 5 Mmol CaCl2;
[0283] 9. Reaction buffer: 1X DNase I buffer, DNase I buffer 20 U / mL, RNasin (RNase inhibitor) 0.05%, enzyme-free water.
[0284] The RNA extraction process consists of two parts: the first part removes the red blood cells, and the second part extracts the RNA;
[0285] The first part of the red blood cell removal is similar to the red blood cell removal process (red blood cell lysis) described above; the specific process of the second part is as follows:
[0286] 1. Add 500uL of lysis buffer and 10uL of proteinase K to the white precipitate obtained after removing red blood cells. Vortex and mix at room temperature for 10 seconds. Let stand at room temperature for 10 minutes, inverting 8-10 times every 3 minutes.
[0287] 2. Centrifuge the centrifuge tube in step 1 above at 12000g for 2 minutes at 4°C and transfer the supernatant to a new centrifuge tube;
[0288] 3. Add 270uL of binding solution and vortex for 3 seconds to mix;
[0289] 4. Add 20uL of magnetic bead suspension and vortex mix for 3 seconds;
[0290] 5. Add 100uL isopropanol, pipette up and down to mix 8-10 times, let it stand for 10 minutes, and invert it 8-10 times every three minutes;
[0291] 6. After low-speed centrifugation, place the tube on a magnetic stand for 2 minutes and remove the supernatant.
[0292] 7. Add 300uL of the third cleaning solution and mix well by pipetting 8 to 10 times;
[0293] 8. After low-speed centrifugation, place on a magnetic stand and let stand for 2 minutes. Remove the supernatant. (If DNA enzyme lysis is required, skip to step 15.)
[0294] 9. Add 700uL of the second cleaning solution and mix thoroughly by pipetting;
[0295] 10. Place on a magnetic stand for 2 minutes and remove the supernatant.
[0296] 11. Repeat steps 9 and 10 once;
[0297] 12. Air dry at room temperature for 5 minutes until there is no obvious liquid on the surface;
[0298] 13. Add 40uL of eluent, mix thoroughly by pipetting, and shake at 1300rpm at room temperature for 5 minutes;
[0299] 14. Place the centrifuge tube on the magnetic stand for 2 minutes and transfer the supernatant to a new centrifuge tube for the next test;
[0300] If DNAse lysis is required, skip from step 8 to step 15;
[0301] 15. Add 100 μL of reaction buffer to the centrifuge tube in step 8 above, mix thoroughly by pipetting, and incubate at room temperature for 15 minutes;
[0302] 16. Add 500 μL of binding solution, mix thoroughly by pipetting, and place on ice for 5 minutes, inverting 10 times every two minutes;
[0303] 17. Place on a magnetic stand and let it adsorb for 2 minutes, then remove the supernatant;
[0304] 18. Repeat steps 9 and 10 twice;
[0305] 19. Let it dry at room temperature for 5 minutes until there is no obvious liquid on the surface;
[0306] 20. Add 60uL to 100uL of eluent, mix thoroughly by pipetting, and shake at 1300rpm at room temperature for 5 minutes;
[0307] 21. Place the centrifuge tube on the magnetic stand for 2 minutes and transfer the supernatant to a new centrifuge tube for the next test.
[0308] The concentration and purity of RNA extracted using polymer microspheres with silanol (-Si-OH) groups on the surface, polymer microspheres with carboxyl (-COOH) groups on the surface, or polymer microspheres with amino (-NH2) groups on the surface were tested to obtain the data in Table 2.
[0309] Table 2: Comparison of RNA extraction performance of polymer microspheres provided in this application
[0310] Among them, the reference group is the polymer microspheres (magnetic beads) in the related art. It can be seen that the recovery concentration of RNA extracted from polymer microspheres with silanol (-Si-OH) groups on the surface and polymer microspheres with DNA amino (-NH2) groups on the surface is comparable to that of the magnetic beads in the related art; in particular, the RNA recovery concentration of polymer microspheres with silanol (-Si-OH) groups on the surface is higher than that of the RNA recovery concentration in the related art, and its RNA purity and RIN value are also higher. It should be noted that each set of data in Table 2 includes 3, and the 3 data are the results of multiple measurements of the same batch of samples.
[0311] The RNA integrity number (RIN) indicator classifies the quality of total RNA of eukaryotes based on the overall electropherogram and sets the RIN value range from 1 to 10, where 1 represents the most severe degradation and 10 represents the most complete.
[0312] In addition, in order to verify the changes in the magnetic responsiveness of the polymer microspheres with silanol groups (-Si-OH) on the surface, the polymer microspheres with carboxyl groups (-COOH) on the surface, or the polymer microspheres with amino groups (-NH2) on the surface provided in the examples of the present application after heating, the magnetic beads of the reference group and the three magnetic beads provided in the present application were heated at 75°C for 15 minutes at the same time, and the magnetic adsorption and magnetic responsiveness of the beads were compared after they were placed on the magnetic stand for 1 minute, 2 minutes, and 5 minutes;
[0313] Figure 12 provides the magnetic adsorption and magnetic responsiveness of each magnetic bead before heating; Figure 13 provides the situation after heating at 75°C for 15 minutes and on the magnetic stand for 1 minute; Figure 14 provides the situation after heating at 75°C for 15 minutes and on the magnetic stand for 2 minutes; Figure 15 provides the situation after heating at 75°C for 15 minutes and on the magnetic stand for 5 minutes; comparing Figures 12-15, it can be seen that the three magnetic beads provided in the embodiments of the present application all have good magnetic adsorption and magnetic responsiveness after heating at 75°C for 15 minutes and on the magnetic stand for 1 minute; the magnetic beads in the reference group are still in a mixed solution state after being heated at 75°C for 15 minutes and on the magnetic stand for 1 minute, and have poor magnetic adsorption and magnetic responsiveness. The magnetic beads in the reference group can only be precipitated after being heated at 75°C for 15 minutes and on the magnetic stand for 5 minutes. Obviously, compared with the magnetic beads in the reference group (in the related art), the three magnetic beads provided in the examples of the present application all have better magnetic stability under heat, indicating that the magnetic particles HC in the magnetic beads (polymer microspheres) provided in the examples of the present application are better dispersed in the dispersion HF, and the interfaces of the magnetic particles are difficult to melt each other under heating conditions.
[0314] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of this application. Therefore, the scope of protection of this application should be based on the scope of protection of the claims.
Claims
1. A polymer microsphere, wherein: It comprises a core body and a shell encapsulating the core body; The core comprises at least two magnetic particles and a dispersion located between two adjacent magnetic particles; the shell comprises a shell body and a modification layer, wherein the modification layer is located on a side of the shell body away from the magnetic particles; The dispersion, the shell body and the modification layer are made of the same material.
2. The polymer microsphere according to claim 1, wherein The dispersion covers at least a portion of the surface of the magnetic particles.
3. The polymer microspheres according to claim 2, wherein The materials of the dispersion, the shell body and the modified layer all include a polymer formed by at least one first monomer and at least one second monomer; the molar ratio of the first monomer to the second monomer ranges from 0.1 to 10.
4. The polymer microspheres according to claim 3, wherein The second monomer and the modified layer both include at least one group selected from the group consisting of amino, carboxyl, hydroxyl and silanol.
5. The polymer microspheres according to claim 4, wherein The molar amount of the second monomer is less than the molar amount of the first monomer.
6. The polymer microspheres according to claim 3, wherein The first monomer includes at least one of styrene, butadiene, pentadiene, isoprene, methyl acrylate, acrylonitrile, methyl methacrylate, and tetraethyl orthosilicate; The second monomer includes at least one of methacrylic acid, ethyleneimine, hydroxyethylpropylene, tetraethyl orthosilicate, vinyl siloxane, N-(4-carboxyphenyl)maleimide, aminopropyltriethoxysilane and glyoxal.
7. The polymer microspheres according to claim 3, wherein The ratio of the mass of the magnetic particle to the sum of the masses of the first monomer and the second monomer is in the range of 0.5-3.
8. The polymer microsphere according to any one of claims 3-4, 6-7, wherein The first monomer includes styrene, the second monomer includes methacrylic acid, and the molar ratio of the first monomer to the second monomer ranges from 0.1 to 10.
9. The polymer microsphere according to any one of claims 3-4, 6-7, wherein The first monomer includes tetraethyl orthosilicate, the second monomer includes aminopropyltriethoxysilane and glyoxal, the molar ratio of the first monomer to the total amount of monomers ranges from 0.1 to 0.8, the molar ratio of aminopropyltriethoxysilane to the total amount of monomers in the second monomer ranges from 0.1 to 0.4, and the molar ratio of glyoxal in the second monomer to the total amount of monomers ranges from 0.1 to 0.
5.
10. The polymer microsphere according to any one of claims 3-4, 6-7, wherein The first monomer includes styrene, the second monomer includes ethyleneimine, the molar ratio of the first monomer to the total amount of monomers ranges from 0.1 to 0.6, and the molar ratio of the second monomer to the total amount of monomers ranges from 0.4 to 0.
9.
11. The polymer microsphere according to claim 1, wherein The distance between the magnetic particle and the modified layer in the direction from the geometric center of the polymer microsphere to the modified layer ranges from 10 nm to 500 nm.
12. The polymer microsphere according to claim 1, wherein The magnetic particles include one or more of iron oxide, cobalt oxide, and nickel oxide, and the size of the magnetic particles ranges from 8 nm to 15 nm.
13. The polymer microsphere according to claim 1, wherein The size of the polymer microspheres ranges from 100 nm to 5 μm.
14. A method for preparing polymer microspheres, wherein: Applicable to preparing polymer microspheres according to any one of claims 1 to 13, the method comprising: forming magnetic particles; The magnetic particles, at least one first monomer and at least one second monomer are mixed together, and the polymer microspheres are formed in one step by in-situ polymerization; wherein the polymer microspheres include a core body and a shell encapsulating the core body; the core body includes at least two magnetic particles and a dispersion located between two adjacent magnetic particles; the shell includes a shell body and a modification layer, and the modification layer is located on a side of the shell body away from the magnetic particles; wherein the materials of the dispersion, the shell body and the modification layer are the same and all include a polymer formed by at least one of the first monomers and at least one of the second monomers.
15. The preparation method according to claim 14, wherein: The step of mixing the magnetic particles, at least one first monomer and at least one second monomer together to form the polymer microspheres in one step by in-situ polymerization comprises: The magnetic particles, one of the first monomers and one of the second monomers are mixed together to form the polymer microspheres in one step by in-situ polymerization; Alternatively, the magnetic particles, one of the first monomers and two of the second monomers are mixed together, and the polymer microspheres are formed in one step by in-situ polymerization.
16. The preparation method according to claim 15, wherein: In the case where the magnetic particles, one of the first monomers and one of the second monomers are mixed together and the polymer microspheres are formed in one step by in-situ polymerization, the step comprises: dispersing the magnetic particles in anhydrous ethanol to obtain a suspension of the magnetic particles; Add polyvinyl pyrrolidone, an initiator and the second monomer to the suspension of the magnetic particles, and introduce a protective gas; add the first monomer after stirring evenly, and continue stirring and reacting at a first preset temperature for 2 to 6 hours; wherein the first monomer includes styrene and the second monomer includes methacrylic acid; After the reaction liquid is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain the polymer microspheres.
17. The preparation method according to claim 15, wherein: In the case where the magnetic particles, one of the first monomers and one of the second monomers are mixed together and the polymer microspheres are formed in one step by in-situ polymerization, the step comprises: dispersing the magnetic particles in anhydrous ethanol to obtain a suspension of the magnetic particles; Adding polyvinyl pyrrolidone, an initiator, the first monomer and the second monomer to the suspension of the magnetic particles; stirring and reacting for 2 to 4 hours under vacuum and a second preset temperature; wherein the first monomer includes styrene and the second monomer includes ethyleneimine; After the reaction liquid is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain the polymer microspheres.
18. The preparation method according to claim 15, wherein: In mixing the magnetic particles, one of the first monomers and two of the second monomers When the polymer microspheres are formed in one step by in-situ polymerization, the step comprises: dispersing the first monomer in anhydrous ethanol; dispersing the magnetic particles in an aqueous solution containing polyvinyl pyrrolidone to obtain a suspension of the magnetic particles; Adding the suspension of the magnetic particles to anhydrous ethanol dispersed with the first monomer, then adding two of the second monomers and ammonia water, stirring evenly and reacting at a third preset temperature for 1 to 3 hours; wherein the first monomer includes tetraethyl orthosilicate, and the second monomer includes aminopropyl triethoxysilane and glyoxal; After the reaction liquid is cooled to room temperature, it is washed with anhydrous ethanol and deionized water, and dried to obtain the polymer microspheres.
19. The preparation method according to claim 14, wherein: The forming of magnetic particles comprises: Mix hydrated ferric chloride, hydrated ferrous chloride and isopropyl alcohol together and stir evenly; Raise the temperature to 50℃±5℃, slowly drop concentrated ammonia water, and stir to react for 10 to 30 minutes; After the reaction is completed, the reaction solution is placed at 0-10°C for 4-6 hours; After washing with methanol, adding a methanol solution in which oleic acid is dissolved, stirring for 2-5 hours, to obtain the magnetic particles; The magnetic particles were washed again with methanol and dispersed in hexane.
20. The preparation method according to claim 14, wherein: The forming of magnetic particles comprises: Mix ferric chloride, ferrous chloride, hydrochloric acid and deionized water together and stir evenly to obtain an iron ion mixed solution; Passing protective gas and dripping the iron ion mixture into the sodium hydroxide solution at 80°C±5°C with continuous stirring, and reacting for 20 to 40 minutes after the iron ion mixture is dripped; After the reaction is completed, the mixture is cooled to room temperature and washed with anhydrous ethanol and deionized water, and then dried to obtain the magnetic particles.
